Does the classification of cerebral palsy influence caries experience in children and adolescents? - Michele Baffi Diniz; Renata Oliveira Guaré; Maria Cristina Duarte Ferreira; Maria Teresa Botti Rodrigues Santos (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the influence of the classification of cerebral palsy (CP) on the caries experience in children and adolescents, and determine the types of teeth most affected by dental caries. Methods: A total of 181 individuals with CP, aged 8.30±4.10 years were examined for dental caries diagnosis in primary, mixed and permanent dentitions. The sample consisted of 96 quadriplegic individuals, 56 diplegic, 18 hemiplegic and 11 with choreoathetosis. The groups were compared using Kruskal-Wallis and Chi-square tests. Univariate logistic regression models were used to identify whether age was a predictor of caries risk (α=5%). Results: The sample was homogeneous as regards sex and age, among patients with quadriplegia, diplegia, hemiplegia and choreoathetosis. Out of the total sample, 51.4% of the individuals were caries free. The overall mean for the dmft and DMFT indices were 1.70±3.30 and 0.70±1.60, respectively. The mean caries experience in primary, mixed and permanent dentitions did not vary significantly according to the CP classification (p>0.05). Child´s age was a predictor for dental caries experience (p<0.05). Conclusions: The CP classification did not influence on caries experience, and the teeth most affected by dental caries were the primary and first permanent molars.